(untitled) (lectio difficilior, 2001)
When feminist scholars engage in scrutinizing the letters of Paul, one expects a critical re-evaluation of the history of their devastating effects on Christian women. But a survey of the last twenty years of feminist scholarly research in Pauline exegesis reveals unexpected dimensions. Apart from criticism of the apostle`s androcentric language and some irrecoverably misogynistic sayings, the Pauline writings offer rich materials for a feminist reconstruction of early Christian history. This reconstructive work has become the starting point for a new reading of „Paul“ as a concept for interpretation in the German-speaking parts of Europe. The hermeneutical foundations for this project are provided by the feminist and critical discussion of the Auslegungsgeschichte, as well as by the questioning of conceptual dualism and the consistent critics of antijudaism. The controversial discussion of Galatians 3,28 by Brigitte Kahl and Elisabeth Schüssler Fiorenza demonstrates the explosive effect of this project to free „Paul“ from an hermeneutics of dominance.